Entrepreneur de soi ou travailleur aliéné ? - Alexis Cukier (Terrains/Théories)
This article questions the Foucauldian analytics of power to conceive the managerial organization of labour in the context of neoliberalism. On the ground of a discussion of some of the main arguments in The Birth of Biopolitics, and in the light of contemporary empirical research in the fields of sociology of work, psychology of labour and the economic theories of the firm, it criticizes the idea according to which the worker today would have actually become an “entrepreneur of the self”. Finally, to describe and criticize the “entrepreneurial discipline” in neomanagement and its typical apparatuses (individual assessments, total quality standards, benchmarking, training in personal development, etc.), it proposes another reactualization of Foucault, grounded in his analysis of strategies, disciplines and blocks of power in “The Subject and Power.”